Two new species and an additional faunistic record of Crenitis Bedel, 1881 from China (Coleoptera: Hydrophilidae: Chaetarthriinae) - Jia, Feng-Long; Mai, Zu-Qi (Zootaxa, 2026)
Two new species of the genus Crenitis Bedel, 1881, Crenitis lianghongbini sp. nov. and C. nezha sp. nov., from the Xizang Autonomous Region and Yunnan Province, China, are described. Crenitis nepalensis Hebauer, 1994 is formally reported in China for the first time. The three species are diagnosed and illustrated, and the key to Chinese species of the subgenus Crenitis s. str. is updated.